Distributed Control Design for Spatially Interconnected Markovian Jump Systems With Time‐Varying Delays. Issue 3 (13th September 2017) - Feng, Hongyan; Xu, Huiling; Xu, Shengyuan; Chen, Weimin
Abstract: This paper focuses on spatially interconnected Markovian jump systems with time‐varying delays. Firstly, a sufficient condition is given to check the well‐posedness, stochastic stability and contractiveness of spatially interconnected systems with the effect of time‐varying delays and Markovian jumping parameters. Secondly, the distributed controllers which inherit the structure of the plants are designed. A sufficient and necessary condition is proposed to guarantee the existence of the distributed controllers. Finally, an illustrative numerical example is given to show the effectiveness of the results.